A communication perspective on interfaith dialogue living within the Abrahamic traditions (Lexington Books, 2013)
"Communication theory provides a compelling way to understand how people of faith can and should work together in today's tumultuous world. In A Communication Perspective on Interfaith Dialogue, fifteen authors present their experiences and analysis of interfaith dialogue and contextualize interfaith work within the frame of rhetorical and communication studies. While the focus is on the Abrahamic faiths, the chapters also include discussion of Hinduism and interracial faith efforts. Each chapter incorporates communication theories that bring clarity to the practices and problems of interfaith communication. Where other interfaith books provide theological, political, or sociological insights, this volume is committed to the perspectives contained in communication scholarship. Interfaith dialogue is best imagined as an organic process and it does not require theological heavyweights gathered for academic banter. As such, this volume focuses on the processes and means by which interfaith meaning is produced."--Page 4 of cover